Losing my religion: how I lost my faith reporting on religion in America-and found unexpected peace - Lobdell, William (HarperCollins Publishers, 2009)
'You need God' -- Born again -- A God thing -- Answered prayers -- Shot out of a cannon -- My Ten Commandments -- Father Hollywood -- A spiritual body blow -- The golden rule -- Millstones around their necks -- A gentle whisper silenced -- 'Rebuild my church' -- Heal thyself -- The dark night of the soul -- At the edge of the earth -- Letting go of God -- One story too many -- 'Welcome to the edge'